Prenatal diagnosis of an 8q22.2-q23.3 deletion associated with bilateral cleft lip and palate and intrauterine growth restriction on fetal ultrasound - Chih-Ping Chen; Tung-Yao Chang; Fang-Yu Hung; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Shih-Ting Lai; Tzu-Yun Chuang; Chen-Chi Lee; Wayseen Wang (Elsevier, 2017)
Objective: We present prenatal diagnosis of an interstitial 8q22.2-q23.3 deletion associated with bilateral cleft lip and palate and intrauterine growth restriction (IUGR) on fetal ultrasound. Case report: A 29-year-old, primigravid woman underwent elective amniocentesis at 17 weeks of gestation because of anxiety. Amniocentesis revealed a karyotype of 46, XX. However, level II ultrasound at 21 weeks of gestation revealed a fetus with IUGR and bilateral cleft lip and palate. Repeat amniocentesis was performed at 21 weeks of gestation, and array comparative genomic hybridization using uncultured amniocytes revealed a 13.5-Mb interstitial deletion of 8q22.2-q23.3 encompassing 37 Online Mendelian Inheritance of in Man (OMIM) genes including SPAG1, GRHL2, NCALD, RRM2B and ZFPM2. Polymorphic DNA marker analysis determined a paternal origin of the deletion. The pregnancy was subsequently terminated, and a malformed fetus was delivered with a depressed nose and bilateral cleft lip and palate. Conclusion: Prenatal diagnosis of facial cleft with IUGR should raise a suspicion of subtle chromosome deletions.